2009
DOI: 10.1021/jp904046h
|View full text |Cite
|
Sign up to set email alerts
|

Pt Flecks on Colloidal Au (Pt∧Au) as Nanostructured Anode Catalysts for Electrooxidation of Formic Acid

Abstract: Nanostructured Pt-on-Au electrocatalysts (coded as Pt m ∧Au, m being the atomic Pt/Au ratio), prepared by Pt deposition on Au colloids in two size ranges (Au-I, 10.0 ± 1.2 nm; Au-II, 3.0 ± 0.6 nm) (Zhao and Xu, Phys. Chem. Chem. Phys. 2006, 8, 5106), were employed for the electrooxidation of formic acid (HCOOH) at concentrations of 0.2−3.2 M by cyclic voltammetry. The HCOOH electrooxidation over a Pt shell fully covering Au-I colloids (Pt m ∧Au-I at m > 0.2, Pt dispersion < 20%) occurred mainly in the high pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 45 publications
3
70
0
Order By: Relevance
“…32 As shown in the CV traces, when the electrode potential was scanned from −0.2 to 1.0 V vs. Ag/AgCl, distinct peaks assigned to the oxidation of formic acid through the efficient formate pathway (see below) were observed at about 0.3 V vs. Ag/AgCl on the Au–Pd alloy, Au@Pd, and Pd NCs. Au NCs scarcely exhibited catalytic activity for formic acid oxidation 33. On the reverse scan, small peaks attributed to the oxidation of adsorbed CO intermediate were observed at 0.6 and 0.5 V vs. Ag/AgCl for Au–Pd NCs and Pd NCs, respectively, were followed by the oxidation of formic acid at similar potentials as those observed in the forward potential sweep.…”
mentioning
confidence: 68%
“…32 As shown in the CV traces, when the electrode potential was scanned from −0.2 to 1.0 V vs. Ag/AgCl, distinct peaks assigned to the oxidation of formic acid through the efficient formate pathway (see below) were observed at about 0.3 V vs. Ag/AgCl on the Au–Pd alloy, Au@Pd, and Pd NCs. Au NCs scarcely exhibited catalytic activity for formic acid oxidation 33. On the reverse scan, small peaks attributed to the oxidation of adsorbed CO intermediate were observed at 0.6 and 0.5 V vs. Ag/AgCl for Au–Pd NCs and Pd NCs, respectively, were followed by the oxidation of formic acid at similar potentials as those observed in the forward potential sweep.…”
mentioning
confidence: 68%
“…3, the reason of signals disappearance could not be no indicator molecules aggregating on the Au surface. It was suggested that electron transfer from the d states of non-SERS active metal oxide (IrO x ) to those of SERS-active substrates (Au) could be responsible for the quenching of the surface plasmon excitations [30].…”
Section: Resultsmentioning
confidence: 99%
“…[35,37] Au is not an effective electrocatalyst towards HCOOH oxidation to CO 2 ( Figure S6 in the Supporting Information); instead, it facilitates the first electron transfer during the direct dehydrogenation process of formic acid oxidation. [38][39][40] Therefore, one possible reason for the unexpectedly high activity for HCOOH oxidation on the Pt-around-Au nanocomposite is the efficient spillover of HCOO from Au to the surrounding Pt NPs, where HCOO is further oxidized to CO 2 . The detailed mechanism for enhanced HCOOH oxidation on the Ptaround-Au nanocomposite is currently under investigation.…”
mentioning
confidence: 99%